Effects of omega-3 on depression: A systematic review (Research, Society and Development, 2026)
Objective: to evaluate the effects of omega-3 and find a consensus in the literature on dose/effectiveness. Methods: systematic review, with searches in databases and virtual libraries: Google Scholar, LILACS, MEDLINE/PubMed, Web of Science, and SciElo, using the terms "omega-3," "stress," and "oxidative stress." Conducted between January and March 2024. Studies that answered the guiding question "Does omega-3 improve depression?" were included. The Inclusion criteria were case-control studies in humans conducted in the last 5 years. Results: omega-3 improves depression and its symptoms. It was observed that the doses of EPA and DHA varied among the studies, but beneficial effects were observed even with low doses. Most studies used standardized questionnaires to measure the degree of depression and specific biomarkers for inflammation. Conclusion: omega-3 supplementation may be beneficial for the prevention and treatment of juvenile, senile, pre- and postpartum depression, closely relating it to inflammation. Future studies should focus on standardizing EPA and DHA dosages and consider the effects of supplement combinations. Omega-3 supplementation should be considered a necessary intervention to reduce the symptoms and occurrence of depression.